2009
DOI: 10.1016/j.jacc.2009.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides Enhance the Production of Adiponectin in Human Adipocytes and in Patients With Chronic Heart Failure

Abstract: Natriuretic peptides enhance adiponectin production by human adipocytes in vitro and even in patients with CHF, which might have a beneficial effect on cardiomyocytes in patients receiving recombinant natriuretic peptide therapy for heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
191
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 37 publications
13
191
3
3
Order By: Relevance
“…However, a recent report showed the natriuretic peptides (atrial natriuretic peptide and BNP) enhance adiponectin production by human adipocytes both in vivo and in patients with heart failure. 29) As we have shown, plasma adiponectin levels were related to plasma BNP levels in this study. Therefore, plasma adiponectin levels might be partially regulated by plasma BNP levels also in patients with HCM.…”
Section: Discussionsupporting
confidence: 68%
“…However, a recent report showed the natriuretic peptides (atrial natriuretic peptide and BNP) enhance adiponectin production by human adipocytes both in vivo and in patients with heart failure. 29) As we have shown, plasma adiponectin levels were related to plasma BNP levels in this study. Therefore, plasma adiponectin levels might be partially regulated by plasma BNP levels also in patients with HCM.…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies suggest that the failing heart acts on fat metabolism by inducing adiponectin secretion and lipolytic actions through the secretion of natriuretic peptides (atrial natriuretic peptide and BNP). 24) At the same time, soluble myostatin released from the failing heart may induce skeletal muscle wasting in HF. 25) However, a direct natriuretic peptide-mediated interaction between the failing heart and muscle has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, atrial natriuretic peptide and BNP, whose levels are increased in HF, might possibly stimulate adiponectin secretion resulting in increased adiponectin levels in patients with HF. Indeed, Tsukamoto et al (25) demonstrated that natriuretic peptides increase the production of Adp by human adipocytes.…”
Section: Discussionmentioning
confidence: 99%